Optimizing the Shape of Welded Constructions Made through the Technique “Temper Bead Welding” - Dobrotă, Dan (Metals (Basel ), 2020)
Welded constructions are subject to high stresses during operation. One solution for improving the behavior in exploitation of welded constructions in various cases is to use the welding technique “temper bead welding” (TBW). In the paper, the optimization of the geometry of the welded joints by the TBW technique was performed. Thus, corner welded joints made of S355 steel were analyzed. To make the welded joints, three layers of welding seams were deposited, and the intermediate layers were processed through cutting with various radii. To analyze the influence of the size of these rays on the behavior of welded constructions, a research program based on factorial experiences was designed. The samples were tested in terms of fatigue behavior by applying loads between ±8 kN and ±12 kN. The research also focused on determining the hardness of the materials in the joints welded and on determining the microstructure of the materials in the heat affected zone (HAZ). Research has shown that it is possible to improve the characteristics of joints made by the TBW technique in the sense that it can be achieved an improvement in fatigue stress, a decrease in the hardness of the HAZ material and an improvement in the metallographic structure of the HAZ material, meaning that it has a structure made of ferrite and fine pearlite.